Encapsulação de óleo essencial de citronela (Cymbopogon winterianus) por gelificação iônica inversa - Benegra, Marjorie (2022)
Citronella essential oil Cymbopogon winterianus is of great commercial interest due to its bactericidal, fungicidal, and repellent properties. However, like all essential oils, they are volatile and susceptible to oxidation. Encapsulation is a process used to isolate assets through a coating or wall and can be used to protect oils, ensuring their stability and preventing loss and degradation. Encapsulation through ionic gelation has advantages because it does not use organic solvents, pH, and temperature extremes at an affordable cost and high charging rate. In this methodology, the composition of the emulsions and the gelling bath are essential for the proper formation of the capsules, such as wall properties, porosity, and thickness. The present work aims to encapsulate citronella essential oil by inverse gelation varying process parameters: drip emulsions and gelling bath. The citronella essential oil used in the study was obtained from steam distillation and characterized by gas chromatography. From the extracted oil, 15 emulsions were formulated, consisting of: 5 mL essential oil, active Tween 0 (0.5%), aqueous CaCl2 solution in different contents (40 g/L, 60 g/L and 120 g/L) pure or enriched with corn starch (0.5%). All emulsions were analyzed for pH, electrical conductivity, zeta potential, optical microscopy morphology, visual stability, and rheology. To obtain the capsules, the emulsions were dropped into sodium alginate solutions (5 g/L or 10 g/L) with or without Tween 80 (0.5%). Drip was done with a 6 mm x 0.25 mm syringe and needle. Distilled citronella oil for the study showed ~75% of citronellal, geraniol, and citronellol. The emulsions were of the water, oil, water (W/O/W) type, showing stability only in the first 5 min after stirring. No significant differences were observed in the viscosity of solutions containing CaCl2. In the alginate bath, the variation in viscosity was significant, an order of magnitude more for the 10g/L content. Of the proposed formulations, 6 formed intact capsules with diameters between 1.6 and 3 mm, which were characterized by optical microscopy, stereoscopy, and scanning electron microscopy (SEM). It was possible to conclude through the stereoscopic images that the addition of Tween 80 in the alginate bath reduced the surface tension, facilitating the penetration of the droplets and resulting in more spherical capsules. The SEM images showed that the addition of corn starch in the emulsion impacted the crosslinking of the alginate with CaCl2 resulting in thicker layers with fewer cracks.